(untitled) (Portuguese Journal of Family Medicine and General Practice, 2022)
Introduction: Better performance in family planning (FP) care would, theoretically, reduce the rates of unwanted pregnancies and, consequently, the rates of voluntary terminations of pregnancy (VTP). Aims: To verify the existence of an association between organizational factors of primary health care (PHC) and the use of VTP consultation at Hospital Beatriz Ângelo, among the women who resorted to it in 2018. Methods: Observational, analytical, and cross-sectional study. Data were collected from the database of a VTP consultation in 2018 and the Electronic Health Record. Descriptive and inferential statistical analysis were performed using SPSS®. Results: About 39.1% of women who underwent a VTP belonged to a UCSP, 38.3% to a USF model A, and 22.6% to a USF model B, with 21.5% not having a family doctor (FD). After data adjustment, we found that users of USF model B or with FD had significantly less VTP (p=0.009 and p=0.001, respectively). USF model B users had more visits to PHC in the 12 months before the VTP (p<0.001) and used more contraceptive methods (p=0.022). Women with FD also used more contraceptive methods in the year before VTP (p<0.001). Conclusions: The better access to PHC and greater use of contraception that is observed among users of USF model B or women with FD are associated with the lower performance of VTP. Having FD but, mainly, belonging to a USF model B, is protective against the realization of VTP, highlighting the need to assign a FD to the entire population, improve accessibility to FP services and encourage organizational autonomy in the PHC setting.